2009
DOI: 10.1063/1.3204137
|View full text |Cite
|
Sign up to set email alerts
|

Generation of warm dense matter and strongly coupled plasmas using the High Radiation on Materials facility at the CERN Super Proton Synchrotron

Abstract: A dedicated facility named High Radiation on Materials ͑HiRadMat͒ is being constructed at CERN to study the interaction of the 450 GeV protons generated by the Super Proton Synchrotron ͑SPS͒ with fixed solid targets of different materials. The main purpose of these future experiments is to study the generation and propagation of thermal shock waves in the target in order to assess the damage caused to the equipment, including collimators and absorbers, in case of an accident involving an uncontrolled release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…5(c) shows that further temperature increase at t ¼ 15 is nominal and in fact the maximum temperature saturates around 9000 K. It is also seen that by this time the heating extends through the entire length of the target. This shows that the material in this region is severely damaged and is in the WDM regime [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: B Hydrodynamic Simulations Using Big2mentioning
confidence: 93%
See 2 more Smart Citations
“…5(c) shows that further temperature increase at t ¼ 15 is nominal and in fact the maximum temperature saturates around 9000 K. It is also seen that by this time the heating extends through the entire length of the target. This shows that the material in this region is severely damaged and is in the WDM regime [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: B Hydrodynamic Simulations Using Big2mentioning
confidence: 93%
“…The primary purpose of the experiments suggested in this paper is to validate the existence of hydrodynamic tunneling that results from the hydrodynamic effects and to gain confidence with the methodology and simulation tools used. At later stages, other areas of research, for example, warm dense matter (WDM) and HED physics [14][15][16][17][18][19][20][21][22][23][24][25], may also benefit from this unique facility.…”
Section: The Hiradmat Facility and The Super Proton Synchrotronmentioning
confidence: 99%
See 1 more Smart Citation
“…The main use of this facility will be to test the consequences of beam impact on beam absorbers, collimators and other objects, which is mandatory for the design of such devices to be installed in LHC and other future accelerator facilities like FAIR, at Darmstadt [12]. These experiments therefore will be very useful to validate our simulations [5][6][7][8][9][10][11] that have been done for the LHC and the SPS beams. In addition to that, other areas of research including material sciences and High Energy Density (HED) states in matter including WDM and SCP [13-15, 17-26, 33, 34] will also benefit from these experiments.…”
Section: Introductionmentioning
confidence: 95%
“…This data is used as input to a two-dimensional hydrodynamic computer code, BIG2 [4], to study the hydrodynamic and the thermodynamic response of the target. These simulations have shown that the target is severely damaged in both cases [5][6][7][8][9][10][11]. A very interesting and important outcome of this work has been that a large part of the target is converted into Warm Dense Matter (WDM) and Strongly Coupled Plasma (SCP) which suggests an additional application of the above two machines.…”
Section: Introductionmentioning
confidence: 95%